2004
DOI: 10.1136/tc.2003.003111
|View full text |Cite
|
Sign up to set email alerts
|

Flying the smoky skies: secondhand smoke exposure of flight attendants

Abstract: Objective: To assess the contribution of secondhand smoke (SHS) to aircraft cabin air pollution and flight attendants' SHS exposure relative to the general population. Methods: Published air quality measurements, modelling studies, and dosimetry studies were reviewed, analysed, and generalised. Results: Flight attendants reported suffering greatly from SHS pollution on aircraft. Both government and airline sponsored studies concluded that SHS created an air pollution problem in aircraft cabins, while tobacco i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 27 publications
2
65
1
1
Order By: Relevance
“…An arrangement on the owners' conception is an issue. Also, smoking restriction methods such as provision of separate seats for children and pregnant women, observed in our study, is considered ineffective (Lambert et al 1993;Repace 2004). To regulate SHS, to reach the knowledge and methods of proper smoking restrictions to every restaurant is necessary, if it did not reach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An arrangement on the owners' conception is an issue. Also, smoking restriction methods such as provision of separate seats for children and pregnant women, observed in our study, is considered ineffective (Lambert et al 1993;Repace 2004). To regulate SHS, to reach the knowledge and methods of proper smoking restrictions to every restaurant is necessary, if it did not reach.…”
Section: Discussionmentioning
confidence: 99%
“…We defined "100% non-smoking" as totally forbidding smoking, and defined "completely non-smoking" as setting aside a separate space using a partition in a restaurant. We judged restaurants that were "100%" and "completely" non-smoking as sufficient to control SHS effectively (Lambert et al 1993;Repace 2004). Other restrictions were defined as insufficient.…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…This presentation is particularly important, since it is the maximum, not the mean, levels that are generally important for regulatory purposes. 85 Another important difference in presentation existed between TNO's report and the published paper. The industry group that met at Covington & Burling in January 1989 had suggested that Malmfors compare measured levels of secondhand smoke components with existing standards.…”
Section: Misleading Presentation Of Resultsmentioning
confidence: 99%
“…These expose the industry's strategies to prevent and obstruct the spread of smoke-free laws, investing in multimillion-dollar campaigns to confuse the public and slow down the rate of decline in cigarette consumption and social acceptability of smoking (Glantz, Barnes, Bero, Hanauer, & Slade, 1995;Muggli, Hurt, & Blanke, 2003). Worldwide, the industry has secretly hired consultants, sponsored symposia, financed research, and engaged in lobbying in order to fuel the controversy on the relationship between SHS and disease (Barnoya & Glantz, 2002;Hammond & Assunta, 2003;Muggli et al, 2003;Repace, 2004a). In recent years, especially in the United States, the industry has shifted the focus to economic claims that smoke-free environments are disastrous for the hospitality industry, investing millions of dollars in restaurant associations (Dearlove et al, 2002) and in the gaming industry (Mandel & Glantz, 2004).…”
Section: The Tobacco Industry and Smoke-free Environmentsmentioning
confidence: 99%
“…' Rights Foundation, 2012). Flight attendants, exposed to extraordinarily high SHS levels in airplanes (Neilsen & Glantz, 2004;Repace, 2004aRepace, , 2004b, were instrumental in spearheading the push for legislation. Their efforts led to the elimination of smoking on U.S. flights.…”
Section: Economic Burden Of Shs Exposurementioning
confidence: 99%